Regional Economic Efficiency In South Sumatera, 2024-2025: A DEA Approach - Ahmad Syaifullah; Wiga Ayu Desmanita; Inne Miftah Dewi (CV. Era Digital Nusantara, 2026)
This study aims to analyze the technical efficiency and scale efficiency of regional economic performance across regencies/cities in South Sumatra Province during 2024-2025 using the Data Envelopment Analysis (DEA) method. This study applies a quantitative approach, with 17 regencies/cities treated as Decision Making Units (DMUs). The input variables include household consumption, government expenditure, investment, and net exports, while the output variable is Gross Regional Domestic Product (GRDP). The findings show that, under the CRS model, the number of efficient regions increased from five in 2024 to six in 2025. Meanwhile, the VRS results indicate that several regions were purely technically efficient but had not yet achieved scale efficiency. Muara Enim, Musi Banyuasin, PALI, Palembang, and Pagar Alam were consistently efficient. DEA projections also reveal that several regions still have potential to improve GRDP, particularly Empat Lawang, Prabumulih, Ogan Komering Ulu, Musi Rawas Utara, and OKU Timur. These findings indicate that regional economic development policies should be directed toward optimizing economic inputs, adjusting the scale of operation, and using benchmarks as a basis for evidence-based policymaking.